Rhein inhibits Chlamydia trachomatis infection by regulating pathogen-host cell - Yu, Xueying; Xu, Qingqing; Chen, Wentao; Mai, Zhida; Mo, Lijun; Su, Xin; Ou, Jiangli; Lan, Yinyuan; Zheng, Heping; Xue, Yaohua (Frontiers in Public Health, 2022)
The global incidence of genital Chlamydia trachomatis infection increased rapidly as the primary available treatment of C. trachomatis infection being the use of antibiotics. However, the development of antibiotics resistant stain and other treatment failures are often observed in patients. Consequently, novel therapeutics are urgently required. Rhein is a monomer derivative of anthraquinone compounds with an anti-infection activity. This study investigated the effects of rhein on treating C. trachomatis infection. Rhein showed significant inhibitory effects on the growth of C. trachomatis in multiple serovars of C. trachomatis, including D, E, F and L1, and in various host cells, including HeLa, McCoy and Vero. Rhein could not directly inactivate C. trachomatis but could inhibit the growth of C. trachomatis by regulating pathogen-host cell interactions. Combined with azithromycin, the inhibitory effect of rehin was synergistic both in vitro and in vivo. Together these findings suggest that rhein could be developed for the treatment of C. trachomatis infections.